"Five-layer gasket seal" watertight closure for reconstruction of the skull base in complex bilateral traumatic intraorbital meningoencephaloceles: a case report and literature review. (12th May 2018) - Zhao, Dan; Tao, Shanwei; Zhang, Dewei; Qin, Mengyang; Bao, Yijun; Wu, Anhua
ABSTRACT: Purpose : Traumatic meningoencephalocele primarily occurs as a rare but complex complication of cranial base and orbital roof fractures. Traumatic intraorbital meningoencephalocele, which is rare and easily overlooked, can be life-threatening since cephalomeningitis occurs due to cerebrospinal fluid (CSF) leakage. It is obscure for the operative indications or standard surgical methods of traumatic meningoencephaloceles since the combined intricate craniofacial and basal fractures, brain injury, and CSF leak may exist. This case report proposes a new operative method for the repair of complex skull base fractures following traumatic intraorbital meningoencephalocele. Methods : A 30-year-old male with a history of complex trauma presented with symptoms of exophthalmos and traumatic CSF rhinorrhea was evaluated via 3D CT of the skull base and brain MRI and was diagnosed with bilateral intraorbital meningoencephaloceles and multiple craniofacial bone, skull base, and orbit fractures. Results : Successful resection of the meningoencephaloceles and reconstruction of the skull base defects were performed via craniotomy using a "five-layer gasket seal" technique that involved, from extracranial to intracranial, a gelatin sponge, muscular paste, vascularized periosteum, RapidSorb Orbital Floor Plate (OrbFloor), and Neuro-Patch layers. Conclusions : The diagnosis and treatment of complex intraorbital meningoencephalocele require careful attention. Resection of herniated tissue is suggested due to potential contamination. The "five-layer gasket seal" watertight closure technique is recommended for successful repair of the skull base in cases involving traumatic meningoencephalocele with complex skull base fractures.